On the ruins of Babel : architectural metaphor in German thought - Purdy, Daniel L. (Signale (Ithaca, N.Y.), 2011)
Purdy surveys the volatile state of architectural theory in the Enlightenment, brought on by the newly emerged scientific critiques of Renaissance cosmology, then shows how German writers deployed Renaissance terminology so that 'harmony' & 'unity' became states of consciousness, rather than terms used to describe the built world.